The Multifaceted Nature of Aminopeptidases ERAP1, ERAP2, and LNPEP: From Evolution to Disease - Paladini, Fabiana; Fiorillo, Maria Teresa; Tedeschi, Valentina; Mattorre, Benedetta; Sorrentino, Rosa (Frontiers in Immunology, 2020)
In the human genome, the aminopeptidases ERAP1, ERAP2 and LNPEP lie contiguously on chromosome 5. They share sequence homology, functions and associations with immune-mediated diseases. By analyzing their multifaceted activities as well as their expression in the zoological scale, we suggest here that the progenitor of the three aminopeptidases might be LNPEP from which the other two aminopeptidases could have derived by gene duplications. We also propose that their functions are partially redundant. More precisely, the evolutionary story of the three aminopeptidases might have been dictated by their role in regulating the renin–angiotensin system, which requires their controlled and coordinated expression. This hypothesis is supported by the many species that lack one or the other gene as well as by the lack of ERAP2 in rodents and a null expression in 25% of humans. Finally, we speculate that their role in antigen presentation has been acquired later on during evolution. They have therefore been diversified between those residing in the ER, ERAP1 and ERAP2, whose role is to refine the MHC-I peptidomes, and LNPEP, mostly present in the endosomal vesicles where it can contribute to antigen cross-presentation or move to the cell membrane as receptor for angiotensin IV. Their association with autoinflammatory/autoimmune diseases can therefore be twofold: as “contributors” to the shaping of the immune-peptidomes as well as to the regulation of the vascular response.